Safety and Toxicity Implications of Multifunctional Drug Delivery Nanocarriers on Reproductive Systems In Vitro and In Vivo - Ahmad, Anas (Frontiers in Toxicology, 2022)
In the recent past, nanotechnological advancements in engineered nanomaterials have demonstrated diverse and versatile applications in different arenas including bio-imaging, drug delivery, bio-sensing, detection, and analysis of biological macromolecules, bio-catalysis, nanomedicine, and other biomedical applications. However, public interests and concerns in the context of human exposure to these nanomaterials and their consequential well-being may hamper the wider applicability of these nanomaterials-based platforms. Furthermore, human exposure to these nanosized and engineered particulate materials has also increased drastically in the last two decades due to enormous research and development and anthropocentric applications of nanoparticles. Their widespread use in nanomaterials-based industries viz. nanomedicine, cosmetics, consumer goods have also raised questions regarding the potentials of nanotoxicity in general and reproductive nanotoxicology in particular. In this review, we have summarized diverse aspects of nanoparticle safety and their toxicological outcomes on reproduction and developmental systems. Various research databases including PubMed and google scholar were searched for the last 20 years up to the date of inception and nano toxicological aspects of these materials on male and female reproductive systems have been described in detail. Furthermore, a discussion has also been dedicated to the placental interaction of these nanoparticles and how these are able to cross the blood-placental barrier and precipitate nanotoxicity in the developing offspring. Fetal abnormalities in consequences to the administration of nanoparticles and pathophysiological deviations and aberrations in the developing fetus have also been touched upon. A section has also been dedicated to the regulatory requirements and guidelines for the testing of nanoparticles for their safety and toxicity in reproductive systems. It is anticipated that this review will incite a considerable interest in the research community functioning in the domains of pharmaceutical formulations and development in nanomedicine-based designing of therapeutic paradigms.